Academic clustering in intercollegiate athletics - McCormick, Kaydee K. (Kansas State University, 2010)
Academic clustering is the occurrence of twenty-five percent or more of a single athletic team enrolled into a major (Fountain & Finley, 2009). Although clustering appears to have the possibility to occur among all college students, it seems to be more prevalent within intercollegiate athletics. There are several different factors that influence the prevalence of this experience. For the collegiate student-athlete, these factors include the National Collegiate Athletic Association, university athletic departments, individual differences among student-athletes, and characteristics associated with the university. While these are likely not the only contributors of academic clustering, they seem to be very prominent. Further, given that attention has been given to identifying the negative consequences of academic clustering in intercollegiate athletics, clustering also may result in positive implications. The purpose of this report is to provide information and increase the awareness towards academic clustering. Additionally, this report provides information as to the causes, but also offers recommendations that have the potential to lessen academic clustering within intercollegiate athletics.
Keywords: Intercollegiate Athletics; Education, Higher (0745)